2014
DOI: 10.1007/s10461-014-0785-0
|View full text |Cite
|
Sign up to set email alerts
|

Declining Prevalence of Probable Depression Among Patients Presenting for Antiretroviral Therapy in Rural Uganda: The Role of Early Treatment Initiation

Abstract: Little is known about trends in depression at antiretroviral therapy (ART) initiation among people living with HIV (PLHIV) in low- and middle-income countries. We used data from an ongoing cohort of treatment-naïve PLHIV in rural Uganda to estimate secular trends in depression among PLHIV at ART initiation. We fitted linear regression models with depression symptom severity as the outcome variable and year of cohort entry (2005–2012) as the explanatory variable, adjusting for socio-demographic variables and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
1
12
2
Order By: Relevance
“…In addition, while other studies in sub-Saharan Africa have also found reductions in depressive symptoms at 12-months after ART initiation, our findings demonstrate a more rapid change in depressive symptoms as well as a decline in HIV-related stigma and an increase in social support during study follow-up (39,41,42). ART use may mitigate depressive symptoms by acting through psychological, behavioral, or biological pathways (39,4145).…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…In addition, while other studies in sub-Saharan Africa have also found reductions in depressive symptoms at 12-months after ART initiation, our findings demonstrate a more rapid change in depressive symptoms as well as a decline in HIV-related stigma and an increase in social support during study follow-up (39,41,42). ART use may mitigate depressive symptoms by acting through psychological, behavioral, or biological pathways (39,4145).…”
Section: Discussioncontrasting
confidence: 46%
“…In addition, while other studies in sub-Saharan Africa have also found reductions in depressive symptoms at 12-months after ART initiation, our findings demonstrate a more rapid change in depressive symptoms as well as a decline in HIV-related stigma and an increase in social support during study follow-up (39,41,42). ART use may mitigate depressive symptoms by acting through psychological, behavioral, or biological pathways (39,4145). For example, regular ART use can result in lower HIV RNA viral loads and higher CD4 counts, improved physical health and quality of life, and reduced general distress, which may in turn lead to less severe depression (39,43,45).…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…Based on the HSCL (cut-off>1.75 with 11–15 items) ( Table 2D ), the pooled prevalence of depressive symptoms among untreated or mixed groups of PLHIV was 24% [95% CI: 22–27] with a high between-group heterogeneity (I 2 = 85%) ( Fig 3D -right) [ 63 65 ]. Some studies specified that they used the scale without somatic symptoms [ 63 , 65 ].…”
Section: Resultsmentioning
confidence: 99%